A retrospective analysis of inotuzumab ozogamicin usage in adult patients with relapsed/refractory B-cell acute lymphoblastic leukemia - Agrawal, Narendra; Boyella, Pavan K.; Bhargava, Rahul; Nair, Chandran K.; Nag, Arijit (Frontiers in Oncology, 2025)
IntroductionThe treatment of B-cell acute lymphoblastic leukemia (ALL) in India involves multi-agent chemotherapy and central nervous system (CNS) prophylaxis, but relapsed/refractory (R/R) B-cell ALL presents with high mortality and limited salvage options. Inotuzumab ozogamicin (InO), a monoclonal antibody targeting cluster of differentiation-22 (CD22) conjugated to calicheamicin, has improved outcomes for R/R B-cell ALL. A phase 3 multicenter trial (INO-VATE) in adult patients with CD22+ B-cell ALL has shown that InO significantly increases response rates and overall survival (OS) compared to standard treatments, with ongoing studies assessing its real-world effectiveness in India.MethodologyA multicentric, retrospective, observational study was conducted across five oncology centers in India to evaluate the effectiveness of InO in adult patients with R/R B-cell ALL. The study aimed to assess clinical outcomes, including the rate of complete remission (CR)/CR with incomplete hematologic recovery (CRi), minimal residual disease (MRD) negativity, duration of remission (DOR), OS, and the safety and tolerability of InO in real-world settings.ResultsThe medical records of adult patients (n = 32) aged >18 years with R/R B-cell ALL treated with InO between February 2017 and October 2022 were assessed. Among the total study participants, 59.4% (n = 19) achieved CR/CRi. Of these responders, MRD negativity was achieved in 94.7% (n = 18/19), and 68.4% (n = 13/19) achieved deep responses (MRD negative CR/CRi) after a median of two cycles of InO. The median DOR for those achieving CR/CRi was 6 months. Of the entire cohort, 34.4% (11/32) of the participants proceeded to hematopoietic stem cell transplantation (HSCT). The OS rates at 6 and 12 months in the entire cohort were 46.9% and 28.1%, respectively. The median relapse-free survival (RFS) among the responders was 7 months. Grade 3/4 treatment-related liver toxicity following InO initiation was reported in 37.5% of the participants. Myelosuppression-related adverse events were observed in 87.5% of the recipients.ConclusionThe real-world study (RWS) highlights the effectiveness of InO in achieving remission and MRD negativity in R/R B-cell ALL, although treatment-related toxicities remain a concern.